Preparation of magnetic and conductive Ni-Gd ferrite-polyaniline composite - Aphesteguy, Juan Carlos (2007)
In this work, particles of NiFe1.95Gd0.05O4 were coated with polyaniline (PANI) during the in situ polymerization of aniline in aqueous solution. Different ferrite/aniline ratios were selected in order to study magnetic and conductivity properties with increasing fraction of PANI. In a previous work, the addition of Gd in the structure of nickel ferrites obtained from mixed Gd, Fe and Ni citrates has been investigated in order to explore the possibility of Gd for Fe substitution in the solids. The ferrite-PANI composites were characterized by X-ray diffraction (XRD) and infrared (IR) spectroscopy. The changes on the magnetic and conductive properties after polyaniline coating were investigated. The coercivity is almost unchanged, while the saturation magnetization drastically decreases. It was found that the conductivity at room temperature increases from 4×10-3 to 9.6×10-3 S/cm when ferrite content changed from none to 24.5 wt/wt%. The conductivity of all measured samples decreased with decreasing temperature, exhibiting typical semiconductor behavior.